Percepções acerca do emprego sinalário disciplinar em libras por professores e alunos surdos - OLIVEIRA, Andriele Praia Rodrigues de (2022)
From the perspective of inclusive education, the inclusion of deaf people in regular education still poses several obstacles. The education of deaf people is a very relevant subject nowadays. Thus, the present research was developed from the perspective of inclusive education. The main objective of this study was to analyze the perception of teachers / interpreters and deaf students in High School, about teaching and learning in Biology classes, using the mobile application "Signal in Libras", and the questions that guided the research were: Is the didactic resource in line with the school curriculum and the requirements of the National Curricular Common Base (BNCC)? And how can it be used as support by the educator? Can the school deficit index of the deaf student be a reflection of the lack of didactic resources? How can ICTs contribute to this change? Being a qualitative research, classified as procedures as a case study. The data were obtained through interviews with Biology teachers (02), interpreters (04) and deaf students (04). The results obtained through the research revealed that the greatest learning difficulties in Biology are related to the difficulty of understanding the signs of biological terminologies, nomenclatures, didactic materials for limited Libras. The application was evaluated regarding the contributions to the teaching / learning process, the data showed that the Libras Signal is an important tool that can be used in the classroom, both by biology teachers, as well as by students and interpreters. Thus, it is important to highlight the importance of using technologies aimed at the inclusion process of deaf students in Biology classes, such as the Libras Signal.